2022
DOI: 10.3389/fonc.2022.966998
|View full text |Cite
|
Sign up to set email alerts
|

Commencing colorectal cancer screening at age 45 years in U.S. racial groups

Abstract: Screening for colorectal cancer (CRC) is cost-effective for reducing its mortality among the average-risk population. In the US, CRC incidence and mortality differ among racial/ethnic groups, with non-Hispanic Blacks (NHB) and American Indian/Alaska Natives showing highest incidence and mortality and earlier presentation. Since 2005, some professional societies have recommended CRC screening for NHB to commence at 45 years or earlier; this was not implemented due to lack of recommendation from key groups that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…These data contributed to the recent move to lower the colorectal cancer screening age to 45 for earlier detection and treatment. 42,43 Our study reported age-adjusted mortality rates instead of crude; therefore, their comparison between age groups would not have provided additional insight.…”
Section: Discussionmentioning
confidence: 99%
“…These data contributed to the recent move to lower the colorectal cancer screening age to 45 for earlier detection and treatment. 42,43 Our study reported age-adjusted mortality rates instead of crude; therefore, their comparison between age groups would not have provided additional insight.…”
Section: Discussionmentioning
confidence: 99%